A Commentary on “Cervical Rotation-Traction Manipulation for Cervical Radiculopathy: A Systematic Review and Meta-Analysis of Randomized Control Trials” [Letter] - Wang Z; Wang X; Jiao H (Journal of Pain Research)
Zeyang Wang,1,2,* Xiaohan Wang,1,3,* Hao Jiao2,3 1School of Anesthesiology, Xuzhou Medical University, Xuzhou, Jiangsu, 221004, People’s Republic of China; 2Department of Anesthesiology, The Affiliated Hospital of Xuzhou Medical University, Xuzhou, Jiangsu, 221002, People’s Republic of China; 3Jiangsu Province Key Laboratory of Anesthesiology, Xuzhou Medical University, Xuzhou, Jiangsu, 221004, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hao Jiao, Department of Anesthesiology, The Affiliated Hospital of Xuzhou Medical University, No. 99 huaihai West Road, Xuzhou, Jiangsu, 221002, People’s Republic of China, Email 13512560960@139.com